Characteristics and Validation of Augmented Reality-Based Learning Media on Hydrocarbon Material for Vocational High School - Vita Fitria Ningrum; Woro Sumarni; Edy Cahyono (Universitas Negeri Semarang, 2021)
The development progress of technology digital very necessary era of learning time is. One of the technologies that can help improve the understanding of the participants of learners is augmented reality. This research is intended for designing and developing media learning-based augmented reality in the material hydrocarbon and validity for determining the feasibility of the media is. The research is a kind of research development using Design Research and Development (R&D). The product validity testing phase was carried out by two material experts and three media experts. In addition, it was done testing the response of the participant students. Mechanical analysis of the data using instrument questionnaire as well as technical analysis of statistical descriptive. The results of the research of this are: 1) the results of the development of media learning-based augmented reality in the material hydrocarbon the form of an application android which consists of five menu main that is KD and indicators, material, AR camera, practice questions, and the identity of the researcher, as well as seven cards molecule from the molecular structure of chemical compounds; 2) the results of the validity assessment by material experts with an average score of 85% in the